Occupational intervention in mental health hospitals: Study of contextual impact. (17th February 2023) - Volovik-Shushan, Shani; Krupa, Terry; Bloch, Yuval; Lipskaya-Velikovsky, Lena
Abstract: Background: Recovery-promoting and occupation-oriented interventions for people with schizophrenia who receive in-patient services are scarcely investigated, limiting our understanding of the factors affecting intervention effectiveness and hindering occupational inclusion. Aims: To investigate the impact of contextual factors on the effectiveness of 'Occupational Connections' (OC) – occupational intervention for in-patient psychiatric settings. Materials and methods: Quasi-experimental, single-blind study compared between inpatients with schizophrenia participating in OC ( N  = 14) and those receiving treatment as usual only ( N  = 16) on primary outcomes of participation dimensions and recovery-orientation of the service, and on secondary outcomes of cognition, symptom severity, and functional capacity. Results: Participation in OC in a new context appears to contribute to improvement in cognitive fluency and flexibility, schizophrenia symptoms, and functional capacity (−2.8< t  < 4.32, p  < 0.05) with no improvement in the participation dimensions (−1.36< t  < 1.36, p  > 0.05) or reduction (−2.25< t  < 3.74, p  < 0.05). The pattern of change in primary and secondary outcomes in a new context was distinct from previous reports on OC effectiveness. Conclusions and significance: These findings suggest the impact of contextual factors on OC effectiveness. Personal participants' factors, institutional features, clinician characteristics, and intervention qualities should be considered in the process of the OC further development, evidence building, and clinical implementation to ensure optimal intervention results.